2008
DOI: 10.1158/1535-7163.mct-07-0524
|View full text |Cite
|
Sign up to set email alerts
|

Ellipticine derivative NSC 338258 represents a potential new antineoplastic agent for the treatment of multiple myeloma

Abstract: High-risk multiple myeloma can be correlated with amplification and overexpression of the cell cycle regulator CKS1B. Herein, we used the COMPARE algorithm to correlate high expression of CKS1B mRNA in the NCI-60 cell line panel with the concentration causing 50% growth inhibition (GI 50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…23 Another ellipticine derivative NSC338258 was shown to exhibit cytotoxicity in myeloma cells independent of topoisomerase II inhibition. 24 These studies are consistent with our findings and suggest that a close derivative to ellipticine might act by different mechanisms to suppress tumors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…23 Another ellipticine derivative NSC338258 was shown to exhibit cytotoxicity in myeloma cells independent of topoisomerase II inhibition. 24 These studies are consistent with our findings and suggest that a close derivative to ellipticine might act by different mechanisms to suppress tumors.…”
Section: Resultssupporting
confidence: 92%
“…Resistance of p53-mutant or -null tumors to conventional radiation and activate the mitochondrial apoptotic pathway. 24 Interestingly, studies have shown that ellipticine has the ability to restore mutant p53 function. An analysis has indicated that ellipticine and its analogs were more potent against cell lines that harbor mutant p53 in growth inhibition assays.…”
Section: Discussionmentioning
confidence: 99%
“…DT204 has been shown to reduce myeloma viability by inducing cell cycle arrest and enhancing the anti-myeloma effect of BTZ in MM cell lines and patient samples [64]. Recently, using the COMPARE algorithm to identify the correlation between CKS1B gene expression and drug activity, Tian et al identified 9-dimethyl amino-ethoxy ellipticine (EPED3), a highly stable compound derivative of the plant alkaloid ellipticine [65]. Studies using MM cells showed that treatment with EPED3 induced cell death.…”
Section: Cks1bmentioning
confidence: 99%
“…Thus, CKS1B amplification may indicate aggressive clinical behavior. Interestingly, some drugs, such as fluoxetine and EPED3, have been reported to have a specific anti-CKS1B activity leading to an antiproliferative tumor cell activity (Krishnan et al, 2008;Tian et al, 2008). The future potential of these therapeutic drugs in the management of malignant neoplasms presenting CKS1B amplification and/or overexpression has to be defined.…”
Section: Cks1b In Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%